PERAN DAN KEDUDUKAN CAMAT DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH MENURUT UNDANG- UNDANG NOMOR 23 TAHUN 2004 TENTANG PEMERINTAHAN DAERAH - Azwan Azwan (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2019)
The main problem of this research is the Role and Position of sub-district heads in the administration of regional government according to law number 23 of 2014, The next problem is, how the role and position of sub-district heads in the administration of regional government according to law number 23 of 2014 and what factors influence leadership camat in carrying out its functions, duties, and authorities according to law number 23 of 2014. This research is a normative legal research that is prescriptive and technical or applied in nature. The research approach uses the law approach and case approach. The type of research data is secondary data with primary and secondary legal materials. Data collection techniques such as literature study and data analysis techniques used are deductive. The results of this study explain that the Role and Position of the Camat in the administration of regional government according to Law Number 23 of 2014 is that the Sub-district is no longer a unit of governmental authority, but rather as a unit of work or service area. The status of the sub-district is now a district / city regional apparatus equivalent to regional offices and technical institutions and even kelurahans. The Camat accepts the delegation as the authority of the Regent / Mayor to handle it as a matter of regional autonomy (delegative authority), the Camat also carries out general governmental duties in accordance with Law No. 23 of 2014. (Attributive authority). Districts are formed as implementing the principle of decentralization.